1999
DOI: 10.1007/s004120050395
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular characterization of a highly repeated DNA sequence in the peach potato aphid Myzus persicae

Abstract: Electrophoresis following digestion of Myzus persicae genomic DNA with HindIII showed the presence of a prominent band of approximately 200 bp whereas a faint electrophoretic band corresponding to DNA fragments of about 3000 bp was observed after digestion with ApaI. In situ digestion with restriction enzymes, followed by in situ nick translation, showed that ApaI targets are localized at the nucleolus organizer-bearing X telomeric region, whereas HindIII restriction sites are clustered in intercalary C-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 32 publications
5
77
1
Order By: Relevance
“…The conspicuous CMA bright band detected at the telo meric region of the largest autosomal bivalent in E. meditabunda together with the fact that the nucleolus, as revealed by silver staining, was associated with the telo meric region of this bivalent, led us to conclude that the NOR region is associated with a GC rich band. This cor respondence between CMA positive banding and NOR regions has also been described in the X chromosome of aphids Mandrioli et al, 1999). In the present contribution the DAPI and CMA bright fluo rescence of the sex chromosomes of E. meditabunda and E. rufomarginata until diplotene is consistent with the allocycly of these chromosomes during male meiosis, and it probably reflects different degrees of chromatin con densation rather than differences in base composition.…”
Section: Discussionsupporting
confidence: 67%
“…The conspicuous CMA bright band detected at the telo meric region of the largest autosomal bivalent in E. meditabunda together with the fact that the nucleolus, as revealed by silver staining, was associated with the telo meric region of this bivalent, led us to conclude that the NOR region is associated with a GC rich band. This cor respondence between CMA positive banding and NOR regions has also been described in the X chromosome of aphids Mandrioli et al, 1999). In the present contribution the DAPI and CMA bright fluo rescence of the sex chromosomes of E. meditabunda and E. rufomarginata until diplotene is consistent with the allocycly of these chromosomes during male meiosis, and it probably reflects different degrees of chromatin con densation rather than differences in base composition.…”
Section: Discussionsupporting
confidence: 67%
“…In several species of Rhynchospora, Vanzela et al (1998) observed the occurrence of multiple rDNA sites always distributed in the terminal regions. Similarly, satellite DNA sequences with generalized equilocal distribution were observed in the holocentric chromosomes of the peach potato aphid (Spence et al, 1998;Mandrioli et al, 1999). Therefore, HC equidistribution may not depend fundamentally on Rabl orientation and band-centromere distance, but rather on some structural or functional similarity of each chromosomal region that makes them equally receptive to the installation and/or amplification of the same or similar DNA sequence (Fry and Salser, 1977;Flavell, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The heterochromatin of holocentric chromosomes, therefore, shows several common features with that of monocentric chromosomes since both contain ATrich satellite DNAs, transposable elements, HP1 proteins and methylated histones (e.g. Ohbayashi et al, 1998;Mandrioli et al, 1999;Cowell et al, 2002;Mandrioli, 2002;Mandrioli, 2003a, b;Mandrioli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%